Perlindungan Konsumen dalam Akad Jual Beli Diskon Akhir Tahun Perspektif Ekonomi Syariah - Harjoni; Karfin; Hasrun, Andi; Mukaromah, Lisa Aminatul; Winarsih, Sri (Al-Mizan, 2024)
The background of this research focuses on consumer protection in the practice of end-of-year discount sales from the perspective of Islamic economics. End-of-year discount practices often do not align with the principles of Islamic economics, which require transactions to be conducted with transparency, honesty, and fairness. This research uses the library research methodology, collecting and analyzing literature related to Islamic economics, consumer protection, and discount practices. The purpose of this research is to analyze the extent of consumer protection in end-of-year discount transactions and identify the application of Islamic principles in these practices. The results show that end-of-year discount practices often neglect Islamic principles such as fairness, transparency, and trustworthiness. Many businesses fail to provide clear product information, which can harm consumers. The study also finds that current regulations do not fully accommodate Islamic values, requiring enhanced oversight and education for both businesses and consumers. In conclusion, integrating Islamic principles into end-of-year discount transactions can improve consumer protection and create a more just economic ecosystem. The contribution of this research is to provide a new perspective for the development of consumer protection policies that align with Islamic economic principles.